Morphology of Streptocara crassicauda and S. recta, with a Review of the Genus Streptocara (Nematoda: Acuariidae) and an Identification Key to Its Species - Yasen Mutafchiev; Boyko B. Georgiev (Diversity, 2023)
The cosmopolitan genus Streptocara Railliet, Henry and Sisoff, 1912 (Nematoda: Acuariidae) comprises parasites of the upper alimentary tract of aquatic and, rarely, terrestrial birds. Two species of the genus Streptocara are redescribed from Bulgaria by means of light and scanning electron microscopy: Streptocara crassicauda (Creplin, 1829), based on specimens from Larus genei, Larus minutus (Laridae) and Aythya ferina (Anatidae), and Streptocara recta (von Linstow, 1879) from Podiceps nigricollis (Podicipedidae). This is the first record of S. recta from Bulgaria. The host and distribution records of the species of the genus Streptocara are reviewed. Six species are recognised as valid. Streptocara crassicauda (Creplin, 1829), S. californica (Gedoelst, 1919), S. formosensis Sugimoto, 1930 and S. incognita Gibson, 1968, seem to be parasites well-adapted to birds of the family Anatidae (Anseriformes) and occasionally found in other birds, whereas S. recta (von Linstow, 1879) and S. longispiculata Gibson, 1968, are specialists of Podicipediformes and Gaviiformes, respectively. Streptocara indica Fotedar and Chishti, 1974, is recognised as a junior synonym of S. crassicauda, and Schistogendra oligopapillata Zhang and An, 2002, is considered as a junior synonym of Streptocara formosensis Sugimoto, 1930. An identification key to the species of the genus Streptocara is proposed.